Utilização da glicerina bruta em rações para frangos de corte - Henz, Jeffersson Rafael (2013)
Three experiments were conducted to determine the nutritional value of crude glycerin and performance of birds fed the residue of biodiesel production. In Experiment 1 360 birds aged 10-20 days were used; as 180 birds from 20 to 30 days, and 144 birds from 30 to 40 days distributed in metabolism cages in a completely randomized design with six treatments and six replications per experimental unit. The total collection of excreta was done to determine the energy values of the crude glicerin. The inclusion levels of the food in the basal diet were 0, 3, 6, 9, 12 and 15%. The AME and AMEn values for stage of 11-20 days ranged from 2723 to 3817 and 2672 to 3666 kcal/kg-1, respectively. In turn, from 21 to 30 days, the AME and AMEn ranged from 3723 to 3982 and 3555 to 3945 kcal/kg-1, respectively. In stage of 31 to 40 days old, the AME and AMEn ranged from 3029 to 4143 and 2975 to 4048 kcal/kg-1 respectively. The values of AMC and AMCn for stage of 11 to 20 days old had a decreasing linear effect, ranging from 87.39 to 62.90 and 84.41 to 61.53%, respectively. In turn from 21 to 30 days, the values of AMC and AMCn had a decreasing linear effect, ranging from 91.70 to 84.30% and 90.80 to 81.40%, respectively. In contrast, from 31 to 40 days, the values of AMC and AMCn had an increasing linear effect, with values ranging from 95.39 to 69.76 and 93.21 to 68.51%, respectively. In Experiment 2 1056 chicks from 1 to 21 days old were distributed in a completely randomized design, with six levels of inclusion of crude glycerin (0, 3, 6, 9, 12, 15%) and eight replicates of 22 birds each. In phase of 1 to 10 days there was a quadratic effect on average feed intake, weight gain, feed conversion and viability. With increasing inclusion of crude glycerin in the diet, there was a linear increase in the moisture content of the bed. In phase of 1 to 21 days, there was a quadratic effect on weight gain, feed intake, feed conversion and viability, and a linear effect on the moisture content of the bed. The chickens fed diets without inclusion of crude glycerin, after the 11th day of age had a superior performance compared to that continued receiving diets containing crude glycerin, regardless of the level of crude glycerin inclusion. In stage of 1 to 10 days, there was no significant effect on the variables of protein deposition and fat in the carcass. In Experiment 3, 960 chicks from 2 to 42 days old were distributed in a completely randomized design, with six levels of crude glycerin inclusion (0, 3, 6, 9, 12, 15%) and eight replicates of 20 chickens each. At the stage of 21 to 35 days there was a quadratic effect on feed intake, weight gain and feed conversion, and a linearly decreasing effect on viability. At the stage of 21 to 42 days, there was a quadratic effect due to the weight gain, feed intake, feed conversion, and an increasing linear effect on the moisture content of the bed. The yield of thigh behaved linearly positive about inclusion levels, while the yield on the thigh had linear effect. On the other hand the performance of wing and abdominal fat behaved quadratically with increasing dietary level of crude glycerin. The rate of fat deposition and dry matter content of the substrate had a decreasing linear effect, since the rate of protein deposition had an increasing linear effect